2020
DOI: 10.7759/cureus.6627
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Pericardial Effusion and Outcomes Post Pericardiocentesis in the Western Region of Saudi Arabia: A Single-center Experience

Abstract: Background Pericardial effusion is the accumulation of blood or excess fluid in the cavity between the heart and the pericardium sac. Pericardial effusion can be caused by several etiologies, including malignant and non-malignant causes. Pericardiocentesis is the gold standard assessment method for pericardial effusion etiology. The aim of this study was to identify the long-term outcome of patients who presented with massive pericardial effusion and underwent pericardiocentesis at King Abdulaziz Medical City,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…Our residents’ perceptions of the applicability of FoCUS and their skills gap ( Table 2 ) are similar to those reported by Canadian IM residency programs [ 8 ]. This may be because, despite the regional differences in the epidemiology of pericardial effusion [ 14 ], for example; use of FoCUS to detect pericardial effusions is applicable worldwide. This observation suggests that international standardization of FoCUS training may be possible and that other countries’ curricula may be relevant in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Our residents’ perceptions of the applicability of FoCUS and their skills gap ( Table 2 ) are similar to those reported by Canadian IM residency programs [ 8 ]. This may be because, despite the regional differences in the epidemiology of pericardial effusion [ 14 ], for example; use of FoCUS to detect pericardial effusions is applicable worldwide. This observation suggests that international standardization of FoCUS training may be possible and that other countries’ curricula may be relevant in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al reported a success rate of 95.5% for echocardiography guided pericardiocentesis [6]. Albugami et al reported re-accumulation of pericardial effusion as high as 21% [7]. Rate of major complications including pneumothorax and myocardial perforation under echocardiographic or fluoroscopy-guided pericardiocentesis is reported to be 0.3 to 3.9% in observational studies [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Khan et al, malignancy was the cause of pericardial effusion in more than 50% of the patients [ 6 ]. In another study from Saudi Arabia, in 48.7% of the patients, malignancy was the cause of the pericardial effusion [ 7 ]. Malignancies and uremia were reported to be the most common cause in the western population [ 8 , 9 ], while Turank et al reported that the most common cause of pericardial effusion is idiopathic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases without pre-existing cancer, malignancy must be excluded because PE may be the rst manifestation of malignancy. Some studies reported PE attributed to unknown causes at a rate of 10-20% [5,6]. It may be di cult to diagnose malignant PE even if cytology or epicardial and pericardial biopsy are performed [7].…”
Section: Introductionmentioning
confidence: 99%